Deglacial to postglacial palaeoenvironments of the Celtic Sea; lacustrine conditions versus a continuous marine sequence - Furze, Mark F.A.; Scourse, James D.; Pieńkowski, Anna J.; Marret, Fabienne; Hobbs, William O.; Carter, Rosemary A.; Long, Brian T. (My University, 2014)
Recent work on the last glaciation of the British Isles has led to an improved understanding of the nature and timing of the retreat of the British−Irish Ice Sheet (BIIS) from its southern maximum (Isles of Scilly), northwards into the Celtic and Irish seas. However, the nature of the deglacial environments across the Celtic Sea shelf, the extent of subaerial exposure and the existence (or otherwise) of a contiguous terrestrial linkage between Britain and Ireland following ice retreat remains ambiguous. Multiproxy research, based on analysis of 12 BGS vibrocores from the Celtic Deep Basin (CDB), seeks to address these issues. CDB cores exhibit a shell-rich upward fining sequence of Holocene marine sand above an erosional contact cut in laminated muds with infrequent lonestones. Molluscs, in situ Foraminifera and marine diatoms are absent from the basal muds, but rare damaged freshwater diatoms and foraminiferal linings occur. Dinoflagellate cysts and other non-pollen palynomorphs evidence diverse, environmentally incompatible floras with temperate, boreal and Arctic glaciomarine taxa co-occurring. Such multiproxy records can be interpreted as representing a retreating ice margin, with reworking of marine sediments into a lacustrine basin. Equally, the same record may be interpreted as recording similar conditions within a semi-enclosed marine embayment dominated by meltwater export and deposition of reworked microfossils. As assemblages from these cores contrast markedly with proven glaciomarine sequences from outside the CDB, a glaciolacustrine interpretation is favoured for the laminated sequence, truncated by a Late Weichselian transgressive sequence fining upwards into fully marine conditions. Reworked rare intertidal molluscs from immediately above the regional unconformity provide a minimum date c. 13.9 cal. ka BP for commencement of widespread marine erosion. Although suggestive of glaciolacustrine conditions, the exact nature and timing of laminated sediment deposition within the CDB, and the implications this has on (pen)insularity of Ireland following deglaciation, remain elusive.
Deglacial to postglacial palaeoenvironments of the Celtic Sea; lacustrine conditions versus a continuous marine sequence